Development of Food Giver Mobile Applications by using Android Studio - Mohd Harith, Muhamad Isshad Danial; Ramli, Nur Ilyani; Siti Zarina Mohd Muji (Evolution in Electrical and Electronic Engineering, 2021)
A statistic provided by Solid Waste Management shows a high percentage of solid waste are disposed at the landfills are comprised of food. It is also reported that Malaysians produce almost 16,000 tons of waste food everyday. The solution that was proposed in this paper is to develop an Android smartphone application that can become a medium for people to give extra food that they have to other people who are in need of food and in at the same time can help to reduce the number of food waste created. The main objectives of this project were to develop an application for Android by using Android Studio software that can reduce food waste and helping those in need. Second, to create an application that is connected to a database where it can store apps and user data. The last objective was to analyse the effectiveness of the applications in terms of apps performance. Android smartphone applications were successfully made where users can post and share their food through the apps to all of the other users. The interface created was user-friendly and the Firebase platform was used as the back-end server for this project. The method that was used in approaching this project is by using the Software Development Life Cycle (SDLC) method where detailed steps were taken during the development of the project. A survey from 50 respondents showed that 78% of the respondents agreed that the development of the apps can reduce food waste and can help other people at the same time. More future recommendations are needed to improvise the efficiency of the app. An app has been successfully created where it can achieve the objectives and tackle the main problem have been created.